St. Stephen's High School an institutional case study - Bala, Nelly (Valdellon) 1921- (s.n.], 1969)
The study attempts to answer the question on how a Chinese high school of the Philippine Episcopalian Church within the jurisdiction of the Foreign Students and Chinese Schools Division, Bureau of Private Schools contributes to the Philippine social life. This study focused on St. Stephen's High School.